The Effect of Speed Agility Quickness (SAQ) Training on Ushiro Mawasih's Kick Speed in Kanas Karate Athletes Dojo Red-Land Halong - Claudia Olivia Manuputty; Albertus Fenanlampir; Johni Melvin Tahapary (Jurnal Ilmiah Wahana Pendidikan, 2023)
Karate is one of the most popular martial arts branches and is in great demand by the public from children to adults, one of the most important basic techniques in karate martial arts is the ushiro mawasih kick technique which requires speed in executing the kick. This study aims to determine the effect of Speed Agility Quikness (SAQ) training on kick speed of Ushiro Mawasih, karate athlete inkanas dojo red-land halong. The research design used the One Group Pre Test Post Test Design. The population in this study were 10 athletes in the Inkanas Dojo Red-Land Halong Karate. Based on the results of data processing and testing using the t-test formula, it turns out that t-count = 7.6820 and t-table for a significance level of 5% = (N-2 = 8) = 1.8595, because t-count > t- table at a significant level of 5%, or 7.6820 > 1.8595, thus Ho is rejected, meaning that there is an effect of Speed Agility Quikness (SAQ) training on kick speed of ushiro mawasih karate athlete inkanas dojo red-land halong. The conclusion based on the results of the discussion above is that the effect of Speed Agility Quikness exercises (scissor hops, lateral jump with two feet and front cone hops) is proven to have shown real effectiveness, meaning that this exercise can increase Ushiro Mawasih's kick speed in Karate athletes in Kanas Dojo Red-land Halong .